EPHEMERAL REVOLUTIONS AND SOCIAL MOVEMENTS IN NIGERIA’S HYBRID DEMOCRACY: FROM OCCUPY NIGERIA TO THE OBIDIENT MOVEMENT - Njoku, Ekeledirichukwu C.; Olemeforo, Ernest Ifeanyichukwu (African Journal of Social and Behavioural Sciences, 2025)
This study advances the concept of ephemeral revolutions to explain why major protest waves and social movements in Nigeria generate intense public mobilisation but fail to produce lasting political or institutional change. Drawing on social movement and hybrid regime theory, it argues that movements such as Occupy Nigeria, EndSARS, and the Obidient Movement exhibit similar trajectories: rapid mass mobilisation, short-lived disruption of state power, and eventual decline driven by elite co-optation, repressive adaptation, institutional weakness, and the volatility of digital organising. Through comparative qualitative analysis, the study shows how each movement illuminates a different facet of ephemerality. Occupy Nigeria demonstrated cross-class alliances, EndSARS – a digitally networked but leaderless structure, and the Obidient Movement, an attempt to channel protest energy into electoral politics – all of which confronted structural limits embedded in Nigeria’s hybrid democracy. The findings refine debates on movement durability in hybrid regimes and suggest that without stronger political institutions, protections for civic space, and mechanisms for post-movement institutionalisation, digital-age mobilisation in Nigeria will continue to yield powerful moments rather than enduring democratic transformations.